Pendidikan Agama Islam Bagi Anggota Polisi Resort Sampang Study kasus di Anggota Polisi Resort Sampang - Moh. Marsuki; Zainuddin Zainuddin (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2022)
Islamic religious education is one of the educations that must be understood by Muslims, therefore it does not look at any institution. This education should be studied properly without exception in the Indonesian National Police Agency and this education is a routine agenda for learning for members of the Police in Sampang and this agenda is based on government regulation number 2 of 2003 concerning disciplinary regulations for members of the Indonesian National Police. This study aims to (1) describe the background of holding Islamic religious education for members of the Sampang Police. (2) Describe the materials and methods in the implementation of Islamic religious education for members of the Sampang Police. (3) Describe the supporting and inhibiting factors in the implementation of Islamic religious education for members of the Sampang Police. This study used a qualitative approach with descriptive methods. The source of the data for this research is the Sampang Police Chief and his staff. The research data were obtained through participatory observation, structured interviews, and document studies. While the data analysis uses the analytical technique, Miles Hiberman. The results of this study indicate that Islamic religious education as in the Sampan Police Station is as follows: 1) the lack of an Islamic religious education agenda for the Sampang Police Station ranks. There is a legal umbrella that accommodates the agenda 2) The material for Islamic religious education that is applied to members of the Resort Police, especially in Sampang includes the study of the interpretation of the Qur'an and the study of Islam. While the method used in the study is the lecture method. 3) The supporting factor in Islamic religious education for Polres members is a program from the Sampang Police and direct orders from the leadership of the Sampang Police Chief. Meanwhile, the inhibiting factor is when it clashes with an urgent task and cannot be left behind.